THE SCHOOL PRINCIPAL’S ABILITY IN CONDUCTING INSTRUCTIONAL SUPERVISION AT UPTD SD NEGERI 7 SAMALANGA, BIREUEN REGENCY - Nanawati, Nanawati; Munawar, Munawar; Iskandar, Iskandar (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Educational supervision is an academic activity in the form of training and development carried out by people who have higher knowledge, aimed at improving teacher interaction in the teaching and learning process. This study aims to determine: 1) the ability of the principal in compiling a supervision program, 2) implementation and 3) evaluation in supervision, 4) obstacles faced by the principal in implementing supervision of teachers. This study uses a descriptive method with a qualitative approach. Data collection techniques used are observation, interviews, and documentation studies. The subjects of the study were the principal, vice principal for curriculum and teachers. The results of the study indicate that: 1) The principal is able to compile a supervision program based on KTSP by referring to BSNP. 2) The implementation of supervision begins with preparing supervision instruments and socializing its activities. The principal in implementing educational supervision involves the vice principal and senior teachers as supervisors. 3) The evaluation carried out in the implementation of supervision is by measuring and comparing supervision instruments such as syllabus and RPP design, learning methods and assessments. 4) The obstacles that occur are that the supervisor's specialization is not the same as the teacher being supervised, so that the results of the supervision implementation are not achieved as expected, and the implementation of supervision has not fully run according to the program that has been prepared, both in terms of the number of visits and the schedule that has been determined